P181 Patient-led remote intracapillary pharmacokinetic sampling (fingerPRICKS) for therapeutic drug monitoring in patients with Inflammatory Bowel Disease. (27th May 2021) - Chee, D; Nice, R; Hamilton, B; Jones, E; Hawkins, S; Redstone, C; Cairnes, V; Pohl, K; Chanchlani, N; Lin, S; Kennedy, N; Ahmad, T; et al.
Abstract: Background: Because of COVID-19 public health restrictions, telemedicine has replaced conventional outpatient follow up for most patients with chronic immune-mediated inflammatory disorders treated with biologic drugs. Innovative solutions to facilitate remote therapeutic drug monitoring are therefore required. Low-volume intracapillary blood sampling can be undertaken by patients at home and samples returned by post to central laboratories. Methods: We sought to report the effect of the COVID-19 pandemic on requests for therapeutic drug monitoring and the equivalence, acceptability and effectiveness of low-volume intracapillary fingerprick sampling compared to conventional venepuncture. Drug and antidrug antibody levels were measured using standard ELISAs. Results: Therapeutic drug monitoring requests for adalimumab (96.5 [70.5 - 106] per week to 52 [33.5 - 57.0], p < 0.001) but not infliximab (184.5 [161.2 - 214.2] to 161 [135 - 197.5], p = 0.34) reduced during the first UK stay-at-home lockdown compared with the preceding six months. Fingerprick sampling was equivalent to conventional venepuncture for adalimumab (Figure 1), infliximab, vedolizumab, and ustekinumab drug and anti-adalimumab and -infliximab antibody levels. The median (IQR) volume of serum obtained using intracapillary sampling was 195µL (130–210). More than 87% (90/103) patients agreed that intracapillary testing was easy and 69% (71/103) preferred it to conventional venepuncture (Figure 2). In routine care, 75.3% (58/77) patients returned two blood samples within 14 days to permit remote assessment of biologic therapeutic drug monitoring. Conclusion: Therapeutic drug monitoring can be undertaken using patient-led remote intracapillary blood sampling and has the potential to be a key adjunct to telemedicine in patients with immune-mediated inflammatory diseases.